2006
DOI: 10.1001/archotol.132.5.501
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Postural Restriction in Treating Benign Paroxysmal Positional Vertigo

Abstract: To investigate the efficacy of postural restriction after canalith repositioning in treating benign paroxysmal positional vertigo (BPPV).Design: Prospective trial of patients with postural restriction vs those without postural restriction after treatment.Patients: Patients with classic BPPV and with BPPV without nystagmus were treated using the modified Epley canalith repositioning procedure. Patients were randomly separated into 2 groups. The first group was instructed to wear a cervical collar and to maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 26 publications
0
57
0
3
Order By: Relevance
“…[10][11][12][13][14][15][16] An important component of the management of BPPV has been the application of postural restrictions after a CRM to prevent the return of otolithic debris into the PSC. 17 Patients are instructed to adhere to postural restrictions for some days. They are to avoid head and trunk movements and are asked to sleep in a semi-seated position with the head inclined at 45° from the horizontal plane for 2 days.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13][14][15][16] An important component of the management of BPPV has been the application of postural restrictions after a CRM to prevent the return of otolithic debris into the PSC. 17 Patients are instructed to adhere to postural restrictions for some days. They are to avoid head and trunk movements and are asked to sleep in a semi-seated position with the head inclined at 45° from the horizontal plane for 2 days.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] The present study was designed to explore the effectiveness of postural restrictions in patients with BPPV caused by otolithic debris in the PSC.…”
Section: Introductionmentioning
confidence: 99%
“…28 We found that postural restrictions do not enhance the beneficial effects of physical treatment with manoeuvres. 29 There is no statistical evidence that restrictions have any role in preventing recurrences, but they often cause neck stiffness, so for these reasons, we do not recommend any restriction to our patients.…”
Section: Final Consideration On Treatmentmentioning
confidence: 66%
“…However, Cakir et al reported that such postural restrictions enhanced the effect of canalith repositioning, when the posterior semicircular canal is involved, especially in resistant cases [16]. This recent prospective study came to a conclusion that seems to be in controversy with all other similar studies.…”
Section: Discussionmentioning
confidence: 82%